Potensi Suplemen dalam Tatalaksana COVID-19 - Lydia Febriana (Cermin Dunia Kedokteran, 2021)
Coronavirus Disease 2019 (COVID-19) merupakan pandemi penyakit baru; berbagai studi dilakukan untuk menemukan terapi yang tepat. Beberapa suplemen juga diteliti potensinya dalam upaya pencegahan ataupun terapi adjuvan COVID-19, antara lain: vitamin C, vitamin D, vitamin E, vitamin B kompleks, zinc, selenium, n-asetilsistein, quercetin, dan melatonin.Coronavirus Disease 2019 (COVID-19) is a new disease pandemic. Several studies are being conducted to find effective therapeutic options. Several supplements are also recommended for their potential in preventing and as adjuvant therapy for COVID-19, including: vitamin C, vitamin D, vitamin E, vitamin B complex, zinc, selenium, n-acetylcysteine, quercetin, and melatonin.